Anxiety and Amnesia: Muslim Women's Equality in Postcolonial India - Vrinda Narain (Faculty of Law Mc Gill University, Montreal, 2005)
ln this thesis, 1 focus on the relationship between gender and nation in post-colonial India, through the lens of Muslim women, who are located on the margins of both religious community and nation. The contradictory embrace of a composite national identity with an ascriptive religious identity, has had critical consequences for Muslim women, to whom the state has simultaneously granted and denied equal citizenship. The impact is felt primarily in the continuing disadvantage of women through the denial of gender equality within the family. The state's regulation of gender roles and family relationships in the 'private sphere', inevitably has determined women's status as citizens in the public sphere. ln this context, the notion of citizenship becomes a focus of any exploration of the legal status of Muslim women. 1 explore the idea of citizenship as a space of subaltern secularism that opens up the possibility for Indian women of aIl faiths, to reclaim a selfhood, free from essentialist definitions of gender interests and prescripted identities. 1 evaluate the realm of constitutional law as a counter-hegemonic discourse that can challenge existing power structures. Finally, 1 argue for the need to acknowledge the hybridity of culture and the modernity of tradition, to emphasise the integration of the colonial past with the postcolonial present. Such an understanding is critical to the feminist emancipatory project as it reveals the manner in which oppositional categories of public/private, true Muslim woman/feminist, Muslim/Other, Western/Indian, and modern/traditional, have been used to deny women equal rights.